Oil Rent and Financial Environment: A Cross-country Examination - Javadi, Shahin; Motevaseli, Mahmood; Farsi, Jahangir Yadolahi (International Journal of Economics and Financial Issues, 2017)
This study provides an empirical investigation to test one of the transmission channels of resource curse, i.e. financial environment. Our panel data analysis of 70 countries from 2006 to 2014 shows a negative and statistically significant association between oil rent and the quality of financial environment in developing countries, but a positive relationship in developed countries. These findings are robust when we control for other major drivers of financial environment quality, unobservable country- and time-fixed effects. In addition, our main results show that institutional quality, among other independent variables, has a major statistically significant effect on financial environment. Keywords: resource curse, oil rents, crowding out, financial market development JEL Classifications: G10; H10